3-Dimensional Physiologic Postural Range of the Mandible: A Computerized-Assisted Technique—A Case Study - Todd Shewman (Case Reports in Medicine)
Previous studies demonstrated that while the mandible assumes its resting position in space, antagonistic muscles should assume minimal muscle activity within a spatial range. This zone of mandibular rest has been mapped using physiologic parameters of muscle activity and incisal spatial kinematics. This case study expands on previous research by monitoring incisal and posterior jaw position and includes lateral pterygoid muscle activity, thus allowing for determining the spatial range including additional relevant coordinates and muscle activity. Four positions were evaluated: a maximum physiologic open position, a maximum physiologic closed position, physiologic rest position, and maximum physiologic protrusion position. Within the physiologic zone of rest formed by these 4 positions, the vertical and anterior borders of the envelope of function may be documented for the incisal and posterior mandible in true 3-dimensional fashion to assist the clinician in determining a physiologic interocclusal freeway space and vertical dimension of occlusion. Advantages and limitations are discussed.